2019
DOI: 10.1002/anie.201900166
|View full text |Cite
|
Sign up to set email alerts
|

Mn‐Catalyzed Dehydrocyanative Transannulation of Heteroarenes and Propargyl Carbonates through C−H Activation: Beyond the Permanent Directing Effects of Pyridines/Pyrimidines

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 102 publications
0
18
0
1
Order By: Relevance
“…Independent studies by the groups of Li and Ackermann revealed Mn(I)‐catalyzed dehydrocyanative domino reactions of 1‐(2‐pyridyl)‐2‐pyridones with propargyl carbonates involving C6−H allenylation. Subsequent Diels‐Alder reactions of the allenyl intermediate on the pyridine followed by retro‐Diels‐Alder and loss of HCN generated fused carbo/heterocycles (Scheme 1a, path C) [8c,d] . Recently, Ackermann and co‐workers reported the reaction of 1‐(2‐pyridyl)‐2‐pyridones with propargyl carbonates under Cp*Co(III) catalysis proceeded through a domino C6−H activation/pyridine directing group migration/alkyne annulation sequence to provide indolizinones (Scheme 1a, path D) [8e] …”
Section: Introductionmentioning
confidence: 99%
“…Independent studies by the groups of Li and Ackermann revealed Mn(I)‐catalyzed dehydrocyanative domino reactions of 1‐(2‐pyridyl)‐2‐pyridones with propargyl carbonates involving C6−H allenylation. Subsequent Diels‐Alder reactions of the allenyl intermediate on the pyridine followed by retro‐Diels‐Alder and loss of HCN generated fused carbo/heterocycles (Scheme 1a, path C) [8c,d] . Recently, Ackermann and co‐workers reported the reaction of 1‐(2‐pyridyl)‐2‐pyridones with propargyl carbonates under Cp*Co(III) catalysis proceeded through a domino C6−H activation/pyridine directing group migration/alkyne annulation sequence to provide indolizinones (Scheme 1a, path D) [8e] …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the involvement of directing groups into the substrate became one of the most promising, effective, and convenient methodologies to achieve highly regio–/stereoselective activation of C–H bonds . For instance, various directing groups, such as ketones, amide, and pyridine, have been applied in selective activation of benzylic C–H bonds and electronically activated alkyl C–H bonds. However, enantioselective functionalization of unbiased methylene C­(sp 3 )–H bonds still represents a formidable challenge that is likely due to similar chemical properties and reaction mechanistic complexity in which subtle changes to the catalyst, substrate, and/or the reaction conditions can alter the reaction stereochemistry .…”
Section: Introductionmentioning
confidence: 99%
“…[14] Moreover,synthesis of 3qq at a2 .5 mmol scale was realized in 71 %y ield. 2-Pyridones functionalized with various electron-donating (OMe,O Bn, NHPh), electron-withdrawing (CF 3 ), alkenyl, and halogen groups at the 3-, 4-, and 5-postions were all effective substrates (3ba-3 oa), generating the products in moderate to high yields.T he compatibility with a5 -alkenyl group indicates tolerance of steric effects.…”
mentioning
confidence: 99%
“…Thecoupling of 2-pyridone 1d and ester 2a (80 8 8C, 1h)a fforded organomanganese complex 8, [14] together with as mall amount of coupled product 3da,thus suggesting that 8 is likely aresting state of the catalyst (Scheme 6a). Thecoupling of 2-pyridone 1d and ester 2a (80 8 8C, 1h)a fforded organomanganese complex 8, [14] together with as mall amount of coupled product 3da,thus suggesting that 8 is likely aresting state of the catalyst (Scheme 6a).…”
mentioning
confidence: 99%